2018
DOI: 10.1159/000492686
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-486 Alleviates Hypoxia-Induced Damage in H9c2 Cells by Targeting NDRG2 to Inactivate JNK/C-Jun and NF-κB Signaling Pathways

Abstract: Background/Aims: Acute myocardial infarction is a serious disease with high morbidity and mortality. microRNAs (miRNAs) have been proved to play an important role in modulating myocardial ischemia and reperfusion injury. Hence, in this study, we constructed H9c2 cell model to elucidate the roles of microRNA-486 (miR-486) in preventing hypoxia-induced damage in H9c2 cells. Methods: H9c2 cells were cultured in hypoxic incubator with 1% O2 to simulate hypoxia and/or transfected with miR-486 mimic, scra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…46 Recent studies demonstrated that NF-κB has cardioprotective effects though repression of apoptotic cell death induced by hypoxia or myocardial injury. [47][48][49] F I G U R E 5 Role of NF-κB in the protective effect of chlorogenic acid against TNF-α injured cardiomyocytes. hiPSC-CMs were treated with QNZ (1 nmol/L) for 4 h or CGA (0.1 μmol/L or 1 μmol/L) for 12 h prior to incubation with TNF-α for 24 h. Then the apoptosis rate of hiPSC-CMs was detected by Annexin V/PI staining, and the quantitative analysis of hiPSC-CMs apoptosis rate is shown (A, B).…”
Section: Discussionmentioning
confidence: 99%
“…46 Recent studies demonstrated that NF-κB has cardioprotective effects though repression of apoptotic cell death induced by hypoxia or myocardial injury. [47][48][49] F I G U R E 5 Role of NF-κB in the protective effect of chlorogenic acid against TNF-α injured cardiomyocytes. hiPSC-CMs were treated with QNZ (1 nmol/L) for 4 h or CGA (0.1 μmol/L or 1 μmol/L) for 12 h prior to incubation with TNF-α for 24 h. Then the apoptosis rate of hiPSC-CMs was detected by Annexin V/PI staining, and the quantitative analysis of hiPSC-CMs apoptosis rate is shown (A, B).…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxia-induced injury model of the H9c2 cells has been widely used in studies on myocardial infarction and ischemia. 21,22 In this study, we also established the myocardial infarction model in the H9c2 cells by treatment under hypoxic conditions for 24 h. Hypoxia-induced injury was investigated according to cell viability and apoptosis. The results showed that hypoxia treatment led to loss of cell viability and an increase in the apoptotic rate.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous regeneration of cardiomyocytes can be induced by exposure to systemic hypoxia 16 . This phenomenon can result in significant functional recovery following MI.…”
Section: Resultsmentioning
confidence: 99%